Optimal control of a dengue epidemic model with vaccination - Rodrigues, Helena Sofia (2011)
We present a SIR+ASI epidemic model to describe the interaction between human and dengue fever mosquito populations. A control strategy in the form of vaccination, to decrease the number of infected individuals, is used. An optimal control approach is applied in order to find the best way to fight the disease.